PERANAN MOHAMMAD HATTA SEBAGAI BAPAK KOPERASI INDONESIA - Resti Damayanti; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The study intends to describe and analyze the background of Mohammad Hatta’s life, the role of Mohammad Hatta in developing cooperation in Indonesia and the obstacles faced by him while he was developing cooperation in Indonesia. The method of this study is a method with a historical, data analysis, and it is an analytical and descriptive study. The result of this study shows that Mohammad Hatta gained modern education in TIS ( Tweedw Inlandsche School ) or Sekolah Ongko Loro, ELS ( Europeesche Lagere School ), HBS ( Hogere Burgere School ) and MULO ( Meer Uitgebreid Lager Onderwijs ). Meanwhile the cooperation experience of Mohammad Hatta started when he became a member of Jong Sumatranen Bond Executive and Joined in foreign university student organization of foreign university student ( Indische Vereeninging ). The roles played by Mohammad Hatta in developing cooperation in Indonesia are when he become the founding father of cooperation, when hw had done reorganization of cooperation, gave advices to the commite of the cooperation congress, developed the cooperation and educated cadres of cooperation. In developing cooperation in Indonesia, Mohammad Hatta also faced many different kind of obstacles.Key Words : Mohammad Hatta, Cooperation Indonesia